Charles Peirce's Theory of Scientific Method - Reilly, Francis E. (Fordham University Press, 2019)
This book is an attempt to understand a significant part of the complex thought of Charles Sanders Peirce, especially in those areas which interested him most: scientific method and related philosophical questions. It is organized primarily from Peirce's own writings, taking chronological settings into account where appropriate, and pointing out the close connections of several major themes in Peirce's work which show the rich diversity of his thought and its systematic unity. Following an introductory sketch of Peirce the thinking and writer is a study of the spirit and phases of scientific inquiry, and a consideration of its relevance to certain outstanding philosophical views which Peirce held. This double approach is necessary because his views on scientific method are interlaces with a profound and elaborate philosophy of the cosmos. Peirce's thought is unusually close-knit, and his difficulty as a writer lies in his inability to achieve a partial focus without bringing into view numerous connections and relations with the whole picture of reality. Peirce received some of the esteem he deserves when the publication of his Collected Papers began more than thirty-five years ago. Some reviewers and critics, however, have attempted to fit Peirce into their own molds in justification of a particular position; others have disinterestedly sought to present him in completely detached fashion. Here, the author has attempted to understand Peirce as Peirce intended himself to be understood, and has presented what he believes Perice's philosophy of scientific method to be. He singles out for praise Peirce's Greek insistence on the primacy of theoretical knowledge and his almost Teilhardian synthesis of evolutionary themes. Primarily philosophical, this volume analyzes Peirce's thought using a theory of knowledge and metaphysics rather than formal logic.